Bibliometric Study: Research Trends in Field of Archives in Jurnal Kearsipan ANRI 2015-2023 - Novelawaty, Yeni Dwi; Lawanda, Ike Iswary (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2024)
This study aims to find out how research trends in archival field. This research describes the development of the number of articles, author productivity, contribution of author institution, and a map of research development in the archival science based on keywords and author collaboration patterns in the Jurnal Kearsipan ANRI 2015-2023. The method used in this research is descriptive quantitative by conducting a search using Harzing PoP software on the Google Scholar database by writing the keyword "archival journal" in the publication name column and narrowing down the research in 2015-2023. Searches are also carried out manually through website Jurnal Kearsipan ANRI. Data analysis using Microsoft Excel and VOSviewer software. The results show that the number of articles has increased in 2015-2017, but it tends to be stable in 2018- 2023. The most productive writer is Dharwis Widya Utama Yacob with 6 article titles. ANRI is the agency that has contributed the most to research in the Jurnal Kearsipan ANRI. The most prominent keywords are record(s) and archive. The results of the co-authors visualization show that there is collaboration between authors with an authorship pattern of 2-4 people. However, the pattern of authorship by one person still dominates. By knowing research trends in archival fields through the Jurnal Kearsipan ANRI 2015-2023, it is hoped that the mapping carried out by the researcher can help provide information to the editorial team of Jurnal Kearsipan ANRI and also to researchers who will next research related archival studies.